2006
DOI: 10.1111/j.1525-1438.2006.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human ovarian carcinoma metastasis by the metastasis-suppressor gene, BRMS1

Abstract: Metastasis-suppressor genes, by definition, suppress metastasis without affecting tumorigenicity and, hence, present attractive targets as prognostic or therapeutic markers. BRMS1 (breast cancer metastasis suppressor) has recently been identified as a metastasis-suppressor gene for human breast cancer and melanoma. Expression of BRMS1 messenger RNA (mRNA) in multitissue including normal prostate, ovarian, testis, and colon has been detected by northern blot analysis. We hypothesize that the role of BRMS1 in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 16 publications
4
71
1
1
Order By: Relevance
“…The Brms1 metastasis suppressor protein (67,68) has been functionally associated with the modulation of phospholipid metabolism. Specifically, Brms1-expressing cells showed significant decreases in endogenous levels of PIP 2 (i.e., <10% of controls).…”
Section: Survival Pathwaysmentioning
confidence: 99%
“…The Brms1 metastasis suppressor protein (67,68) has been functionally associated with the modulation of phospholipid metabolism. Specifically, Brms1-expressing cells showed significant decreases in endogenous levels of PIP 2 (i.e., <10% of controls).…”
Section: Survival Pathwaysmentioning
confidence: 99%
“…Further studies have since shown that BRMS1 is not only a metastasis suppressor gene in breast cancer models but also in various other cancers such as melanoma and ovarian cancer [7,8,9]. Recent studies have also demonstrated that low levels of BRMS1 protein correlated with poor prognosis in cancer patients with advanced disease [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed, in both NSCLC cell lines and human specimens, that the reduction of BRMS1 in NSCLC is secondary to RelA/p65-mediated methylation of the BRMS1 promoter (19,20). The importance of BRMS1 in suppressing metastases has been demonstrated in melanoma, breast, hepatocellular, and ovarian carcinomas (18,(21)(22)(23)(24). BRMS1 has been shown to function as a corepressor to inhibit NF-B transactivation through deacetylation of the RelA/ p65 subunit at K310 (25).…”
mentioning
confidence: 99%